Relationship between lipid profiles with carotid intima--media thickness in children with type I diabetes mellitus - Rubiana Sukardi; Bambang Madiyono; Sudigdo Sastroasmoro; Jose RL Batubara (Indonesian Pediatric Society Publishing House, 2016)
Background The major cause of morbidity and mortality in patients with type I diabetes mellitus is premature and extensive artherosclerosis. Carotid intima-media thickness (IMT) is associated with cardivascular risk factors and has been used as a marker of early artherosclerosis process. Objective To determine IMT of carotid artery and its relationship with duration of diabetes, lipid profiles, and mean HbA 1 level. Methods A cross-sectional study was conducted on patients with type 1 DM at the Department of Child Health Cipto Mangunkusumo Hospital. Ultrasound B-mode imaging was performed to measure the IMT. Age-matched non-diabtetic subjects served as controls. Statistical significant was assumed at P<O.S. Results The mean IMT values of type I DM patients aged < 12 years, 12-18 years, 18+ years were 0.44 (SD 0.03) mm; 0.46 (SD 0.01) mm; 0.51 (SD 0.01) mm, respectively, which were significantly greater than those of age-matched non-diabetic subjects which were 0.39 (SD 0.01), 0.41 (SD 0.01) mm, 0.46 (SD 0.01) mm, respectively. Patients with type I DM had a higher apolipoprotein-Band HDL cholesterol levels than in non- diabetic subjects. Multiple regression analysis showed that there was no relationship between total cholesterol, cholesterol LDL, chronic hyperglycemia (HbA 1) and IMT. However, IMT in type I diabetes was linearly related with duration of diabetes . Conclusion Type I DM patients have greater IMT and higher mean apolipoprotein B. There is a strong correlation between IMT and duration of diabetes.